PENGARUH METODE LATIHAN HIGH INTENSITY INTERVAL TRAINING TERHADAP KECEPATAN PEMAIN FUTSAL GONGXI AKADEMI - Marcello Okan Hidayat; Deka Ismi Mori Saputra; Raja Bani Pilita (Master of Physical Culture and Recreation in Nusantara, 2025)
This study aims to determine the effect of the High Intensity Interval Training (HIIT) method on improving the sprint speed of futsal players at Gongxi Academy. Speed is one of the crucial physical components in futsal, considering the dynamic nature of the game, its fast tempo, and limited playing space which requires players to perform short sprints with high intensity. The research method used was an experimental design with one group pretest-posttest design. The subjects consisted of 20 futsal players from Gongxi Academy. The research instrument was a 60-meter sprint test conducted twice, namely the pretest before treatment and the posttest after treatment. The HIIT program was carried out over 12 sessions with systematically structured training variations. Data were analyzed using the Shapiro-Wilk test for normality and the paired sample t-test for hypothesis testing with the help of SPSS software. The results showed a significant improvement in sprint speed after the players underwent HIIT training. The mean pretest result was 9,83, while the mean posttest result improved to 9.34. Hypothesis testing produced a value of t count = 10.763 > t table = 1.729 with a significance level of 0.000 (< 0.05). Therefore, it can be concluded that HIIT training has a significant effect on improving the sprint speed of futsal players at Gongxi Academy.